Observation of room‐temperature out‐of‐plane switchable electric polarization in supported 3R‐MoS2 monolayers. Issue 2 (9th December 2022) - Ma, Li; Yang, Liu; Fang, Yuqiang; Xu, Manzhang; Duan, Ruihuan; Zhang, Vanessa Li; Wang, Xuewen; Huang, Fuqiang; Wu, Menghao; Liu, Zheng; Yu, Ting
Abstract: Two‐dimensional (2D) ferroelectrics have attracted considerable attention due to their potential in the development of devices of miniaturization and multifunction. Although several van der Waals (vdW)‐layered materials show ferroelectricity, the experimental demonstrations of ferroelectric behavior in monolayers are very limited. Here we report the observation of room‐temperature out‐of‐plane switchable electric polarization in supported MoS2 monolayers exfoliated from 3R‐stacked bulk crystals under ambient conditions. Using in situ piezoelectric force microscopy and Kelvin probe force microscopy in a glovebox, we reveal that trapped water/ice molecules are responsible for this switchable electric polarization and this conclusion is strongly supported by theoretical simulations. It is worth noting that the water/ice trapping in the monolayers exfoliated from 2H‐stacked MoS2 crystals is not as much as that in 3R monolayers and, consequently, the out‐of‐plane electric polarization is missing there. Our findings indicate that monolayers with a trapped single layer of polar molecules might be emerging alternatives to 2D ferroelectrics. Furthermore, the stacking sequences may bring new properties and applications to 2D vdW materials not only when we stack them up but also when we thin them down. Abstract : Using in situ piezoelectric force microscopy and Kelvin probe force microscopy in a glovebox, we probed the MoS2 monolayers exfoliated from 3R‐ and 2H‐stacked bulk crystals under ambient conditions. Our observation indicates that water/ice molecules might be trapped by the 3R‐monolayer MoS2 and this trapping layer may be responsible for out‐of‐plane switchable electric polarization. Our theoretical study also supports this.